Reverse Conformational Changes of the Light Chain-binding Domain of Myosin V and VI Processive Motor Heads During and After a Hydrolysis of ATP by Small-angle X-ray Solution Scattering - Sugimoto, Yasunobu (2009)
We used small-angle X-ray solution scattering technique to investigate the nucleotide-mediated conformational changes of the head domains (subfragment-1 (S1) ) of myosin V and VI processive motors that govern their directional preference for motility on actin. Recombinant myosin V-S1 with two IQ motifs (MV-S1IQ2) and myosin VI-S1 (MVI-S1) were engineered from Sf9 cells using a baculovirus expression system. The radii of gyration (R(g)) of nucleotide-free MV-S1IQ2 and MVI-S1 were 48.6 Å and 48.8 Å, respectively. In the presence of ATP, the R(g) value of MV-S1IQ2 decreased to 46.7 Å while that of MVI-S1 increased to 51.7 Å, and the maximum chord length of the molecule decreased by ca. 9% for MV-S1IQ2 and increased by ca. 6% for MVI-S1. These opposite directional changes were consistent with those occurring in S1s with ADP and Vi or AlF(4)(−2) bound (i.e., in states mimicking the ADP/Pi bound state □ of ATP hydrolysis). Binding of AMPPNP induced R(g) changes of both constructs similar to those in the presence of ATP, suggesting that the timing of the structural changes for their motion on actin is upon binding of ATP (the pre-hydrolysis state) during the ATPase cycle. Binding of ADP to MV-S1IQ2 and MVI-S1 caused their R(g) values to drop below those in the nucleotide-free state. Thus upon the release of Pi, the reverse conformational change could occur, coupling to drive the directional motion on actin. The amount of R(g) change upon the release of Pi was ca. 6.4 times greater in MVI-S1 than in MV-S1IQ2, relating to the strain sensing nature of the ADP state of MVI motor during its translocation on actin. Atomic structural models for these S1s based upon the ab initio shape reconstruction from X-ray scattering data were constructed, showing that MVI-S1 has the light chain-binding domain (LBD) positioned in the opposite direction to MV-S1IQ2 in both the pre- and post-powerstroke states. The angular change between the LBDs of MV-S1IQ2 in the pre- to post-powerstroke states was ~50°, comparable to that of MII-S1. On the other hand, that of MVI-S1 was ~100°, much less than the currently postulated changes to allow the maximal stroke size of myosin VI-S1, but still significantly larger than other myosins reported so far. The results suggest that some additional alterations or elements are required for MVI-S1 to take maximal working strokes along the actin filament.